Manajemen Operasional Paket Wisata City Tour Surakarta di PT. Kirana Surya Gemilang Yogyakarta (Studi Kasus Rombongan Ikatan Wanita Bank Yogyakarta) - Edwin Hastawi Atmaja (Sekolah Vokasi, Universitas Gadjah Mada, 2017)
Tourism is one reliable sector in Indonesia. It’s great contribution for being the second place of the biggest source foreign exchange after oil and gas. This final assignment report is to eximine about the operational management city tour package of one travel agent in one tourist city in Indonesia. This research is purposed to know details the operational management of city tour package in Kirana Tour Yogyakarta. This research used the cualitative method with participatory in collecting data. So with participatory research,researcher could analyze the problems of this research lively. This reseach showed that the operasional management of city tour package could be seen from how the way to answer or react what the consument want, counting technic of basic cost, tour perform and the evaluation after finishing the tour. Kirana Tour was success to build consument satisfication by creating operational management.